AKTIVITAS SISWA DALAM PEMBELAJARAN SOSIOLOGI DENGAN MODEL AKTIF TIPE GROUP TO GROUP EXCHANGE ( GGE) DI SMA NEGERI 2 BATANG KAPAS - Afrigusni, Reri - (Pendidikan Sosiologi, 2014)
This research is motivated by the following issues: (1) in the learning of students who asked still very little, (2) at least the students who proposed the idea of learning, (3) lack of attention to students when teachers convey the material in the learning process. The formulation of the research is how the activity of students in sociology with a model Actively Type Group to Group Exchange (GGE) in SMA N 2 Batang Kapas and this study aims to determine the activity of the students in the learning process sociology with an active learning model type of group to group exchange in SMA N 2 Batang Kapas. This type of research is descriptive quantitative research. Data collection techniques were collected by observation that has been provided with a checklist mark (â). Based on the data analyst obtained the following results, that the indicators were observed on the last observation the average student activity categorized either where there are two indicators are categorized as good of reading, a summary, and five indicators of well categorized once as for all indicators are categorized as either indicators ask questions, express opinions, discussion, listening to the presentation materials and listen to the discussion indicator, so it can be concluded that the activity of the students in the learning process sociology better than before by using a model of the type of group to group active exchange (GGE), from the observations that have been made students in learning activities categorized as good and kind, as well as students tend to be active in the learning process.